Urgensi Kebijakan Mengenai Upaya Hukum Gugatan Atas Sengketa Kepabeanan - Herman, KMS; Kartika, Tantri; Fauzi Februari, Buana; Beni Lumenta, D. (JURNAL RETENTUM, 2023)
This study discusses the unclear regulation regarding legal remedies for lawsuits in resolving customs disputes in Indonesia, as well as its impact on the legal system and protection of the rights of the parties involved. Although the Customs Law has regulated objection and appeal channels, there are no clear regulations regarding the lawsuit mechanism as a follow-up legal remedy. This ambiguity has the potential to cause legal uncertainty, hinder the dispute resolution process, and reduce protection of the rights of the parties involved, such as importers, exporters, and other related parties. This study also compares it with the legal systems of other countries and provides recommendations for improving regulations in order to create legal certainty, justice, and efficiency in resolving customs disputes. This study suggests that lawsuit regulations be included in the Customs Law to strengthen the supervision and law enforcement system, and increase public trust in the customs system in Indonesia.